Genotype-by-trait association of sorghum (Sorghum bicolor (L.) Moench) advanced lines grown under arid and semi-arid regions of Zimbabwe - Mukondwa, Olivia; Manjeru, Pepukai; Ngirazi, Savemore; Mavankeni, Busiso Olga; Kutywayo, Dumisani; Kamutando, Casper Nyaradzai (Korean Society of Crop Science, 2021)
Inadequate information is available on trait relations and profiles of sorghum genotypes, yet this information is vital for precise decisions to be undertaken in breeding programs. Here, 17 sorghum experimental lines were evaluated together with three checks at five locations, representing the major sorghum production environments in Zimbabwe. Across site analysis of variance (ANOVA) showed significant genotypic effects on grain yield (GYD) as well as the other traits, including panicle length (PL) and stem diameter (SD). Distance-based clustering indicated the possibility of indirectly selecting for GYD using; SD, exertion (EXSTN), panicle length (PL), panicle width (PW) and number of leaves (NL). In addition, the vector view of the genotype-by-trait (GT) biplot also revealed strong correlations between GYD and, PW, SD and FYD, as well as the other physiological traits including, days to male flowering (DMA) and days to physiological maturity (DPM). Genotypes superior for a combination of traits were, G6, G7, G11, G18 and G20, which were strong for GYD, PL and PW, as well as, G5 which was strong for sugar content (SC), number of leaves (NL) and SD. Genotypes 15, 16 and 17, were specifically strong for GYD whereas, genotypes 4 and 9 were strong for FYD. Overall, results revealed the key traits which can be considered singularly or in combination, when selecting suitable sorghum genotypes, either for feed or food purposes, under arid and semi-arid conditions. This information is vital for decision making in sorghum breeding programs.